Spinal subdural haematomas in children with non-accidental head injury. Issue 3 (19th August 2008) - Koumellis, P; McConachie, N S; Jaspan, T
Abstract : Objective: To examine the incidence of spinal pathology in infants with non-accidental head injury. Methods: 18 infants with non-accidental head injury were investigated between 2000 and 2007 with dedicated MRI of the brain and spine. During the earlier years, the spine was imaged only when there were suspicious features on other imaging to suggest a spinal injury (seven cases). After 2005, all suspected cases of non-accidental head injury were routinely investigated with MRI of the whole spine in addition to the brain. The spinal imaging at initial investigation and at follow-up was reviewed. Results: There was a high incidence (8/18 cases, 44%) of subdural collections in the spine. They were all clinically occult and in six cases large. All eight cases were associated with subdural haematomas in the supratentorial and infratentorial compartment. The signal characteristics were analysed and compared with those of the intracranial collections. One had a small epidural haematoma. Other depicted abnormalities and appearances at follow-up were also reviewed. Conclusion: There is a high incidence of previously unsuspected spinal subdural haematomas associated with intracranial collections in children with non-accidental head injury. Further work is required to evaluate the clinical implications.